Evaluating Electron and Vibrational Distributions in N\(_2\) Flowing Discharges and Post-discharges at Reduced Gas Pressure - André Ricard; Mario Capitelli (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Relaxation of the electron and vibrational distribution functions have been calculated in function of residence time in N2 electrical discharges and post-discharges. Calculations results are compared to the measurements of N2 radiative states intensity and N2(X,v) vibrational density by CARS in an N2 DC positive column where the following plasma parameters: electron density, gas temperature and electric field have been measured. In the discharge, the vibrational temperature gets bigger with the residence time for t < 10 -2 s. In the post-discharge, the vibrational distribution is evolving in such a manner that the high levels are overpopulated as the low vibrational level populations are dropping.